STRATEGI PENINGKATAN PELAYANAN PUBLIK DENGAN APLIKASI SISTEM INFORMASI KEPENDUDUKAN TERPADU KANTOR PENGADILAN AGAMA PALANGKA RAYA: Strategy for Improving Public Services with the Application of Integrated Population Information Systems Palangka Raya Religious Court Office - rika yunita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The Palangka Raya Religious Court is one of the judicial institutions that administer judicial power. In order to improve the performance of employees at the Palangka Raya Religious Court in providing public services, an application was created that is expected to facilitate the community in changing their marital status after divorce. The application is an Integrated Population Information System (Sidudu). With the SIDUDU application, it is hoped that it will raise the good name of the performance of public servants at the Palangka Raya Religious Court Office in relation to helping accelerate changes in population identity. This researcher is conducting qualitative research, and the data collection techniques used are interviews, observation, and documentation. This study is expected to explain and describe the impact of using the SIDUDU application (strengths and weaknesses) in public services at the Palangka Raya Religious Court office. the use of the SIDUDU application as a strategy for improving public services at the Palangka Raya Religious Court Office, to make it easier for the community, so that the community is served very quickly and can cut bureaucracy. by only bringing a statement from the PA. With the integrated application, the use of the SIDUDU application as a strategy for improving public services at the Palangka Raya Religious Court Office is very helpful for employees in carrying out their main tasks. and daily functions. and can minimize collusion, corruption, and nepotism.